Evidence based measures for reduction of maternal and child mortality in developing countries (2009)
Improving maternal and child health in developing countries are critical components of the millennium development goals. The indicators for measuring progress in most developing countries remain poor reflecting poor access to quality maternal and child health care among other factors. Cost-effective interventions to save women's and children's lives are known. Failure to implement these interventions contributes significantly to the poor health indices prevalent in developing countries. Initiatives for improving quality of maternal and child health care must incorporate affordable and cost-effective evidence-based treatment strategies that are applicable in developing countries.